FEATURES OF PETITION FOR TAKING THE MEANS OF SECURING A CLAIM IN CIVIL PROCEDURE - Grigoryan, Gohar (State and Law, 2022)
This article is devoted to the institution of securing a claim, in particular to the grounds for taking such means. This research is based on analytical and comparative methods. Taking into account the important role and significance of this institution, the purpose of this article is to study in more depth the features of petition for taking the means of securing a claim provided by law. We studied the domestic legislation and theoretical sources, got acquainted with the legislative regulations of other countries and the views of their authors.